PELAYANAN PUBLIK BAGI PEMENUHAN HAK-HAK DISABILITAS DI KOTA YOGYAKARTA - Sugi Rahayu; Utami Dewi (NATAPRAJA, 2013)
This research aims to analyze public policy and service implemented to people with disability. This research is important and interesting because of lack of government’s attention in fulfilling the rights of people with disability.This qualitative descriptive research shows that Yogyakarta City Government has made serious effort to give friendly public service to people with disability. Education Office has launched inclusive education program to give them opportunity to access equal and indiscriminative education. Furthermore, the presence of Blind Corner in Arpusda shows City Government’s effort to equalize them. In term of health, there is Jamkesmas special for people with disability, even though in its practice it is still rarely used by the group. In term of social, Social, Labor, and Transmigration Office has given some aids and capital mentoring every month to families with disability and employed them. The presence of Transjogja and special vehicle for them is effort to equalize them in society. However, programs to make friendly service have not been optimum because of the obstacles in its implementation. Human resource barrier, budget and people’s stigma toward people with disability make fair public service implementation is less effective. Keywords: public service, disability, Yogyakarta City.